Dose Reduction in Molecular Breast Imaging With a New Image-Processing Algorithm - Tao, Ashley T; Hruska, Carrie B; Conners, Amy L; Hunt, Katie N; Swanson, Tiffinee N; Tran, Thuy D; Manduca, Armando; Borges, Lucas; Maidment, Andrew D A; Lake, David; Johnson, Matthew P; Carter, Rickey E; et al. (American journal of roentgenology (1976), 2020)
The purpose of this study was to determine whether application of a proprietary image-processing algorithm would allow a reduction in the necessary administered activity for molecular breast imaging (MBI) examinations. Images from standard-dose MBI examinations (300 MBq Tc-sestamibi) of 50 subjects were analyzed. The images were acquired in dynamic mode and showed at least one breast lesion. Half-dose MBI examinations were simulated by summing one-half of the dynamic frames and were processed with the algorithm under study in both a default and a preferred filter mode. Two breast radiologists independently completed a set of two-alternative forced-choice tasks to compare lesion conspicuity on standard-dose images, half-dose images, and the algorithm-processed half-dose images in both modes. Relative to the standard-dose images, the half-dose images were preferred in 4, the default-filtered half-dose images in 50, and preferred-filtered half-dose images in 76 of 100 readings. Compared with standard-dose images, in terms of lesion conspicuity, the half-dose images were rated better in 2, equivalent in 6, and poorer in 92 of 100 readings. The default-filtered half-dose images were rated better, equivalent, or poorer in 13, 73, and 14 of 100 readings. The preferred-filtered half-dose images were rated as better, equivalent, or poorer in 55, 34, and 11 of 100 readings. Compared with that on standard-dose images, lesion conspicuity on images obtained with the algorithm and acquired at one-half the standard dose was equivalent or better without compromise of image quality. The algorithm can also be used to decrease imaging time with a resulting increase in patient comfort and throughput.